2015
DOI: 10.1097/mao.0000000000000814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Skin Thickness on Cochlear Input Signal Using Transcutaneous Bone Conduction Implants

Abstract: Hypothesis Intracochlear sound pressures (PIC) and velocity measurements of the stapes, round window, and promontory (VStap/RW/Prom) will show frequency dependent attenuation using magnet-based, transcutaneous bone-conduction implants (TCBCI) in comparison to direct-connect, skin-penetrating implants (DCBCI). Background TCBCIs have recently been introduced as alternatives to DCBCIs. Clinical studies have demonstrated elevated high-frequency thresholds for TCBCIs as compared to DCBCIs; however, little data ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
8
36
0
Order By: Relevance
“…specimen 48R), similar to previous observations (Nakajima et al 2009). Nevertheless, H Diff was generally consistent with the previous reports (Greene et al 2015; Mattingly et al, 2015; Nakajima et al, 2009) in the range of frequencies tested previously.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…specimen 48R), similar to previous observations (Nakajima et al 2009). Nevertheless, H Diff was generally consistent with the previous reports (Greene et al 2015; Mattingly et al, 2015; Nakajima et al, 2009) in the range of frequencies tested previously.…”
Section: Resultssupporting
confidence: 92%
“…Recent technological advances have allowed direct measurement of intracochlear pressure in response to sound stimulation in intact human temporal bones (Greene et al 2015; Mattingly et al, 2015; Nakajima et al, 2009; Olson, 1998; Olson, 1999). In this report we set out to characterize ossicular motion and intracochlear pressure in response to low frequency and high level sound stimulation, with particular focus on identifying nonlinearities.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies by our group evaluated the transfer function magnitudes in response to ipsilateral and contralateral BC stimuli (unpublished data). 16 Figure 2A demonstrates the average transfer function magnitudes in each specimen for ipsilateral and contralateral BC. Comparison of the ipsilateral and contralateral bone conduction transfer functions demonstrated that contralateral stimulation results in a 5–15 dB reduction in transfer function magnitude, primarily with high frequency stimuli (see Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The method of sound stimuli production and response recording was performed in similar fashion to previously described protocols. 14, 16 Stimuli were generated digitally, presented to the specimen via a bare (i.e., no sound processing) BC transducer or a closed-field magnetic speaker (MF1; Tucker-Davis Technologies Inc., Alachua, FL, U.S.A.) powered by one channel of a stereo amplifier (SA1; Tucker Davis Technologies Inc., Alachua, FL, U.S.A.) and driven by an external sound card (Hammerfall Multiface II; RME, Haimhausen, Germany) modified to eliminate high-pass filtering on the analog output. Stimuli were generated and responses were recorded at a sampling rate of 96,000 Hz and controlled by a custom program in Matlab (MathWorks Inc., Natick, MA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, ICSP in mammals has been measured with: piezoelectric sensors [9] in cats; piezoresistive sensors [10]- [12] in guinea pigs; and fiber-optic based sensors [5], [13]- [16] in gerbils. In human cadaver heads, ICSP has been quantified with strain gauges [17] and fiber-optic based sound pressure sensors [18], [19]. However, the broader application of existing ICSP measurement methods is limited by laborious sensor preparation, sensor sensitivity changes related to biomaterial deposits on the sensing elements, complexity of the experimental ICSP measurement setup, and low sensor SNR.…”
Section: Sensor Designmentioning
confidence: 99%